Implementasi Proses Asuhan Gizi Terstandar, Pemberian Diet Tinggi Kalori dan Tinggi Protein pada Pasien Bronkopneumonia: Sebuah Laporan Kasus - Nurul Qomariyah; Amila Nurdin; Qonita Rachmah (Universitas Airlangga, 2023)
Background: Bronchopneumonia is a type of pneumonia that occurs in the bronchi and alveoli. Patients with infectious diseases, such as bronchopneumonia, need special nutritional care to speed up recovery and maintain their current weight. The nutrition care process is carried out by providing a high-calorie and high-protein diet to support the fulfillment of intake according to patient needs. Objectives: To find out the implementation of the nutritional care process by administering a high-calorie and high-protein diet to bronchopneumonia patients. Methods: This study was conducted in October 2022 for patients hospitalized at RS X Sidoarjo. Data collection are carried out by observation for 3 days in the domains of food intake, physical/clinical, biochemical, and anthropometry. Results: After the nutrition intervention with the principle of a high-calorie, high-protein diet, the patient's condition began to improve, marked by increased intake from day to day, even though on the first day of intervention there was fulfillment of protein, fat, and iron, which had not been able to reach the target (<60%). The symptoms of cough and cold felt by the patient have decreased in scale, and no weight loss has occurred. However, during the intervention, laboratory tests were not repeated. Conclusions: The patient's recovery in this case was quite fast, the results of clinical physical monitoring slowly improved, no weight loss occurred, and food intake increased gradually towards the set target. Although biochemical values cannot be monitored and evaluated because there has been no re-examination, overall, the nutritional intervention provided was achieved.